RC beams strengthened with longitudinal and U-wrap FRP - Pham, Thong; Hao, Hong (2016)
This study investigates the strengthening efficiency of modified reinforced concrete (RC) beams strengthened with longitudinal and U-wrap FRP. Two types of sections were studied, namely normal rectangular and modified sections. The RC beams were made of normal-strength concrete and then strengthened with different wrapping schemes, including longitudinal FRP layers and FRP U-wraps. The variables of this study are the thickness of FRP layers, the number of FRP U-wraps, and wrapping schemes. These specimens were tested under quasi-static loads until failure. The longitudinal strain and debonding mechanism of FRP are investigated. Experimental results have shown that the proposed modified section not only eliminates the stress concentration at the corners but also provides confinement to the longitudinal FRP layers. Thus, the modified beams showed higher load carrying capacity than that of normal-section beams even though the same amount of strengthening material had been used. Using FRP U-wraps together with modified section can maximize the effectiveness of longitudinal FRP layers. The strain of longitudinal FRP layers and U-wraps was also examined.